1999
DOI: 10.3109/02841859909175564
|View full text |Cite
|
Sign up to set email alerts
|

CT Measurement of Lung Density

Abstract: Quantitative CT provided the means to study noninvasively the electron density of the lung and the factors that influence this value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Posterior lung-tobackground ratio (as well as posterior signal-to-noise and contrast-to-noise ratios) was constantly higher than the anterior lung-to-background ratio (respectively anterior signal-tonoise and contrast-to-noise ratios) for all patients independent of age, as previously shown in the literature [34][35][36][37]. In addition, the lung-to-background ratio of the middle lung part appeared to be lower than the anterior lung-to-background ratio, agreeing with previous findings [38] that showed that the average density of the lung region near the thoracic wall was lower than the average density of the whole lung because the middle region-of-interest was placed near the thoracic wall. The linear regression fit for the two age groups, newborns to 2 years and older than 2 years, showed that the posterior intensity was higher than the anterior intensity.…”
Section: Discussionsupporting
confidence: 92%
“…Posterior lung-tobackground ratio (as well as posterior signal-to-noise and contrast-to-noise ratios) was constantly higher than the anterior lung-to-background ratio (respectively anterior signal-tonoise and contrast-to-noise ratios) for all patients independent of age, as previously shown in the literature [34][35][36][37]. In addition, the lung-to-background ratio of the middle lung part appeared to be lower than the anterior lung-to-background ratio, agreeing with previous findings [38] that showed that the average density of the lung region near the thoracic wall was lower than the average density of the whole lung because the middle region-of-interest was placed near the thoracic wall. The linear regression fit for the two age groups, newborns to 2 years and older than 2 years, showed that the posterior intensity was higher than the anterior intensity.…”
Section: Discussionsupporting
confidence: 92%
“…These opposing effects of smoking are not surprising, and are probably explained by smoking induced inflammation with increased movement of plasma and inflammatory cells from the circulation into the lung interstitium in the short-term and in the long-term remodelling and loss of lung tissue. The opposing effects of smoking on lung density may also explain the inconsistent results of previous cross-sectional studies [7][8][9]. In order to avoid large inter-individual variations, CT-measurements of participants who changed their smoking habits were excluded from the date of change.…”
Section: Discussionmentioning
confidence: 92%
“…Measurement of lung density by computed tomography (CT) is a surrogate marker for emphysema and reflects both disease severity [2][3][4] and physiological impairment [5][6]. Crosssectional studies of the influence of smoking on lung density by CT have reported inconsistent results, with some researchers finding no influence of smoking habit on lung density [7], while others report decreased lung density with increasing pack-yrs [8][9]. This is not surprising given the fact that smoking has opposing effects on lung density.…”
mentioning
confidence: 99%
“…These methods work well for relatively homogeneous lesions, but show the need for intensive user correction for inhomogeneous lesions. For example, most stage I and stage II lung tumours present as homogenous, high-intensity lesions on a background of low-intensity lung parenchyma [ 48 , 49 ] and, therefore, can be automatically segmented with high reproducibility and accuracy. However, for partially solid, ground-glass opacities, nodules attached to vessels and to the pleural surface, automatic segmentation is burdened by low reproducibility [ 50 ].…”
Section: Impact Of Image Segmentationmentioning
confidence: 99%